Teacher Education In India: A Critical Analysis - Ahmad, Jasim (Voices of Teachers and Teacher Educators, 2018)
India is experiencing fast and sudden changes in teacher education in recent times. In 2015, the one year B.Ed. Programme was converted into two year Programme and was implemented in the same year abruptly, without much preparation. The stakeholders of teacher education have been busy in deliberating and discussing about the pros and cons of 2-year B.Ed. programme, meanwhile it is announced that from the session 2019, the 4-Year Integrated B.Ed. Programme will be launched across India. It seems to be a stage of turmoil in teacher education. Teacher educators, pupil-teachers and all other stakeholders are in a state of dilemma about what actually is going to happen and if implemented, how it will be executed in B.Ed. colleges and universities’ department of teacher education. The status of teacher education which gives direction and decides the fate of school education must be crystal clear in its vision and mission. The present paper tries to revisit the development of teacher education in India, analyses present challenges, prevailing curriculum framework, eligibility criteria for teacher educators, and foresee some probable wayout for overcoming this scenario.